Power and transcendence: a comment on upland pioneers - Sprenger, Guido (Social anthropology, 2021)
Upland pioneering involves variations of two themes: drawing in power from the outside and the transcendence of local bounded social entities. Both integrate the distinction between inside and outside at the base of sociality in upland Southeast Asia. Pioneering is a valorised activity that continuously takes on new forms and thereby exemplifies the dynamics of inside and outside. Data from the Rmeet in Laos show that these movements have a gendered dimension.